2020
DOI: 10.1097/mao.0000000000002696
|View full text |Cite
|
Sign up to set email alerts
|

Pain After Cochlear Implantation Without Signs of Inflammation: A Systematic Review

Abstract: Objectives: This review summarizes current evidence on causes and management strategies for delayed pain post-cochlear implantation (CI) surgery, without clinical evidence of inflammation or infection. Methods: The systematic review was undertaken in line with Preferred Reporting Items for Systematic review and Meta-Analysis Protocols 2015 guidelines. A literature search was undertaken, with inclusion of patients who underwent CI and presented with dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In reviewing the literature on causes and management strategies for delayed pain post cochlear implantation (CI) surgery, without clinical evidence of inflammation or infection, it was found that oral therapy (analgesia, nonsteroidal anti-inflammatories, antibiotics) and local treatments (topical, injections) resolved pain in 41% and 63% of patients, respectively. A total of 33% of patients in this review required explantation of the device, with complete resolution of pain in all of these patients (Sethi et al, 2020). Additionally, for the patient described in the present case report, the pain diminished at the first follow-up visit after implant removal.…”
Section: Clinical Considerationsmentioning
confidence: 68%
“…In reviewing the literature on causes and management strategies for delayed pain post cochlear implantation (CI) surgery, without clinical evidence of inflammation or infection, it was found that oral therapy (analgesia, nonsteroidal anti-inflammatories, antibiotics) and local treatments (topical, injections) resolved pain in 41% and 63% of patients, respectively. A total of 33% of patients in this review required explantation of the device, with complete resolution of pain in all of these patients (Sethi et al, 2020). Additionally, for the patient described in the present case report, the pain diminished at the first follow-up visit after implant removal.…”
Section: Clinical Considerationsmentioning
confidence: 68%
“…For this purpose, the authors set checkpoints for up to 5 years after surgery. Considering the work by Sethi et al (9), which showed that the mean time from CI to the onset of pain was 5 years, it is possible that our rates may reflect an underestimation of general DPCIP. The study has two additional main limitations: First, as in other studies on children, the pain evaluation is based on the parental reports regarding their children's pain, rather than direct reports from the children, which may have altered the true prevalence.…”
Section: Limitationsmentioning
confidence: 86%
“…They suggested that pain, unrelated to stimulation or usage, should be considered a major complication, given that half of their cases became temporary non-users, and some underwent reimplantation. In a recent meta-analysis conducted by Sethi et al (9), it was found that the mean time from CI to the onset of pain was 60 months (both adults and children). In all patients, physical examination was documented as unremarkable, and mostly without hearing deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 A recent review and meta-analysis showed that conservative treatment using medical therapy was successful in treating pain in 41% of patients. 24 However, device replacement was effective in 100% of patients. In the current study, we focused on individuals who underwent explantation with the goal of determining an underlying cause of pain.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review and meta‐analysis showed that conservative treatment using medical therapy was successful in treating pain in 41% of patients 24 . However, device replacement was effective in 100% of patients.…”
Section: Discussionmentioning
confidence: 99%